2016
DOI: 10.1200/jco.2016.67.3061
|View full text |Cite
|
Sign up to set email alerts
|

Plasma ESR1 Mutations and the Treatment of Estrogen Receptor–Positive Advanced Breast Cancer

Abstract: ESR1 mutation analysis in plasma after progression after prior AI therapy may help direct choice of further endocrine-based therapy. Additional confirmatory studies are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
526
1
13

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 624 publications
(565 citation statements)
references
References 22 publications
25
526
1
13
Order By: Relevance
“…It has been reported that patients treated with AIs are more likely to develop tumors harboring ESR1 mutations, resulting in ligand-independent transcriptional activity of ER (27,32). In addition, some ESR1 mutations can lead to conformational changes of ER, leading to decreased binding of tamoxifen, thereby potentially reducing its activity (29,31).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that patients treated with AIs are more likely to develop tumors harboring ESR1 mutations, resulting in ligand-independent transcriptional activity of ER (27,32). In addition, some ESR1 mutations can lead to conformational changes of ER, leading to decreased binding of tamoxifen, thereby potentially reducing its activity (29,31).…”
Section: Introductionmentioning
confidence: 99%
“…No difference in the primary endpoint of progression-free survival (PFS) was seen between the three arms. Subsequent prospective-retrospective analysis of ESR1 mutation status in archival plasma circulating tumor DNA (ctDNA) indicated improved outcomes with fulvestrant compared with exemestane among patients with ESR1 mutations, whereas no difference was seen in patients who were ESR1 wild type (Fribbens et al 2016). These results indicate a potential role for ESR1 mutation status in selecting endocrine therapy in patients with HR+ MBC, ideally with re-evaluation of mutation status at any new 'decision point' in the sequence of endocrine therapies.…”
Section: Fulvestrant Clinical Studiesmentioning
confidence: 94%
“…These mutations have clear therapeutic relevance, as functional analysis in both the Toy and Jeselsohn studies revealed relative resistance to tamoxifen and fulvestrant, which could be partially abrogated with increased dose. Analysis of ESR1 mutations has been performed on archival plasma samples of patients with HR+ MBC and prior nonsteroidal AI treatment participating in two large randomized phase II studies (Fribbens et al 2016). These analyses indicated mutation rates of 25% among patients with progression on endocrine therapy in the PALOMA3 study (rising to 29% in patients with prior AI therapy) and 39% among patients with prior AI sensitivity in the SoFEA study.…”
Section: Mechanisms Of Resistance: Esr1 Mutationsmentioning
confidence: 99%
“…5 ESR1-status does not appear to determine response to selective oestrogen receptor downregulators. 58,59 However, preclinical studies revealed relative resistance of the mutations to tamoxifen and fulvestrant but effective inhibition with high doses. [60][61][62][63][64] Retrospective analyses of ESR1 mutations in baseline plasma circulating tumour DNA from completed clinical trials suggest that these mutations are prognostic and predictive of resistance to aromatase inhibitors in metastatic disease.…”
Section: Clinical Decisions For Treatment Strategymentioning
confidence: 99%